‘Real men’ doing dirty work: implications for change - Workman-Stark, Angela L. (Policing and society, 2022)
Police organisations in Canada and other parts of the world, have recently undertaken efforts to address misconduct arising from high-profile reports of internal discrimination and harassment and/or instances of excessive use of force. However, these actions tend to be pursued through traditional approaches without fully understanding the contextual factors that contribute to these harmful behaviours. Through a sequential, qualitative mixed-methods study involving Canadian police officers, this paper highlights how symbolic meanings attached to police work contribute to perceptions that the work is more suitable for some individuals than others. The findings also illustrate how officers respond to identity threats from stigmatised officers or from external sources. Finally, the findings suggest that the prototypical image of a police officer may be changing with recent criticisms of the police presented as possibilities for change.